Pendekatan Holistik dalam Manajemen Pendidikan Islam Untuk Pembentukan Karakter Siswa - Dian Eka Priyantoro; Basri; Khodijah (CV. Creative Tugu Pena, 2026)
This study aims to analyze the implementation of a holistic approach in Islamic education management at SMPN 2 Anak Ratu Aji, Central Lampung, for the character development of students. The background of this research is driven by the need to integrate character education with Islamic values in the learning process. This study uses a qualitative approach with a case study design, collecting data through in-depth interviews, observation, and documentation. The findings of the study indicate that the implementation of the holistic approach has resulted in positive changes in students' character, including improvements in moral attitudes, ethics, discipline, and socia4l skills. Although there are challenges related to limited resources, student acceptance of the approach, and managerial and structural issues, the positive impact on students' character is evident. The main conclusion of this study is that holistic Islamic education is effective in shaping students' character, not only making them academically intelligent but also morally upright and ready to contribute to society.